An investigation into the effect of COVID-19 on the spatial dimension of a South African university town: the case of Westdene - Macua, Kamau (Department of Civil Engineering, 2024)
This research explores the effect of the coronavirus disease 2019 (COVID-19) on the spatial dimension of Westdene, a residential neighbourhood adjacent to the largest campus of University of Johannesburg (UJ), the Auckland Park Kingsway (UJ APK) Campus, defined as a university town. Notably, studies on university towns conceptualised the associated social, cultural, economic and physical factors, collectively referred to as the spatial dimension, through studentification and destudentification. More specifically, studentification and destudentification were used to describe transformations within university towns attributable to increasing and decreasing student populations, respectively. Although reports highlight effects of COVID-19 on various aspects of society, there is no empirical evidence on its effects on the spatial dimension of Westdene; this university town is located in Johannesburg, the largest city in South Africa. This paucity thus warrants an investigation into the effect of COVID-19 on the spatial dimension of Westdene, through the conceptual lens of studentification and destudentification. To provide answers to the theoretical concepts, an embedded single-case study approach, employing a multi-method qualitative research approach, was adopted for the empirical exploration. This research design enabled the investigation of real-world contextual conditions within Westdene, using interviews and field observations. The interviews focused and reflected on the experiences and interpretations of owners of UJ-accredited privately owned student accommodation (POSAs), owners/representatives of local businesses, and members of community engagement and policing forums. Photographs taken in the field complemented the interviews by depicting various aspects of and within Westdene relevant to the study, including: UJ APK Campus and its associated student facilities; identifiable private student housing; local businesses; public space and infrastructure; general state of the environment; and neighbourhood safety and security measures. Notably, the rationale for the choice of the techniques and procedures encapsulated by the effective research methodology were underpinned by theoretical concepts of effective research designs and ethical research. The findings in respect of the spatial dimension of Westdene prior to the COVID-19 pandemic primarily supported studentification literature, given various occurrences noted in Westdene, including: rapid population and demographic restructuring; increased criminal activities; incompatible lifestyles; increased business activity; and increased physical and environmental issues. Contrastingly, the advent of COVID-19 led to various occurrences noted in Westdene that primarily supported destudentification literature, including: student depopulation; fluctuating levels of criminal activities; decrease in student activities; decreased business activity; and decreasing neighbourhood maintenance. Notwithstanding these occurrences, some current and potential ‘positive' occurrences were also noted in Westdene, which invalidated the proposition that COVID-19 (only) negatively affected the spatial dimension of Westdene. These findings thus bring to the fore further critical propositions, buttressed by the existing body of knowledge, for which further research is required.